Recombinant Human Erythropoietin for Kidney Transplantation: A Systematic Review and Meta-Analysis - Zhou, Jiaojiao; Lu, Jing; Cai, Diming (Urology Journal, 2020)
Purpose: The protective effect of recombinant human erythropoietin (rHuEPO) on kidney transplantation has not been established. Therefore, we conducted a systematic review and meta-analysis to evaluate the potential influence of rHuEPO on transplanted kidneys. Materials and methods: To identify relevant studies, we searched electronic databases (PubMed, Medline, EMBASE, Ovid, the Cochrane Library, and major nephrology journals) from inception until June 15, 2018. Two independent reviewers assessed study quality. The systematic review and meta-analysis were performed with fixed- or random-effects models according to heterogeneity, and results are expressed as risk ratios (RR) or weighted mean differences. Results: Six randomized controlled trials with a total of 435 patients met the inclusion criteria. rHuEPO, compared with placebo, had no statistically significant effect on delayed graft function (RR = 0.89, 95% confidence interval [CI] , 0.73 to 1.07; P = 0.22) and slow graft function (RR = 0.93, 95% CI, 0.60 to 1.43; P = 0.73). The rHuEPO and control groups did not differ in thromboembolic events, mortality, acute rejection, and blood transfusion. A significant difference was found in long-term estimated glomerular filtration rate (RR = 3.65, 95% CI, -4.45 to 11.75; P = 0.003). Conclusion: Our findings suggests that rHuEPO has a limited nephroprotective effect in patients undergoing kidney transplantation and does not increase the susceptibility to adverse events.